Amecameca, 1922. Ensayo sobre centralización política y Estado nacional en México - Aboites Aguilar, Luis; Morales Cosme, Alba (El Colegio de México, A.C., 1999)
After describing the 1921-1922  conflict between federal and local government over the  waters of the Amecameca River, this article studies the appropriation and use of productive resources in a town that managed to reach 1920 with a considerable availability of land, water and forests. The authors emphasize the difficult relations between the  town  government and the  town or neighborhood, as  well  as  the   post-revolutionary agrarian reform. They consider that  studying these subjects might lead to new ways of approaching the  National State's formation process, without leaving out colonial and Porfirian elements.